Serpins in Tick Physiology and Tick-Host Interaction - Abbas, Muhammad Nadeem; Chlastáková, Adéla; Jmel, Mohamed Amine; Iliaki-Giannakoudaki, Evangelia; Chmelař, Jindřich; Kotsyfakis, Michail (Frontiers in Cellular and Infection Microbiology, 2022)
Tick saliva has been extensively studied in the context of tick-host interactions because it is involved in host homeostasis modulation and microbial pathogen transmission to the host. Accumulated knowledge about the tick saliva composition at the molecular level has revealed that serine protease inhibitors play a key role in the tick-host interaction. Serpins are one highly expressed group of protease inhibitors in tick salivary glands, their expression can be induced during tick blood-feeding, and they have many biological functions at the tick-host interface. Indeed, tick serpins have an important role in inhibiting host hemostatic processes and in the modulation of the innate and adaptive immune responses of their vertebrate hosts. Tick serpins have also been studied as potential candidates for therapeutic use and vaccine development. In this review, we critically summarize the current state of knowledge about the biological role of tick serpins in shaping tick-host interactions with emphasis on the mechanisms by which they modulate host immunity. Their potential use in drug and vaccine development is also discussed.